Keabsahan Identitas dalam Administrasi Kependudukan - Afdhal Afdhal (JURNAL AKTA YUDISIA, 2020)
Abstract This study aims to identify and explain the purpose of sticking client fingerprint To identify and explain the legal status of fingerprints on Electronic citizen Card (E-KTP) with sticking client fingerprint on the public administration.The research was conducted as an Empirical legal research with socio-legal research approach. The data were collected using structured interview techniques. Data were analyzed qualitatively.The results of the study explained that the purpose of sticking clien fingerprint has not completely realized the legal assurance the correct fingerprint, consequently administration can not use the fingerprint data effectively. Fingerprints used by notaries and fingerprints appear on electronic citizen card have a legal status as authentic evidence of the a citizen’s identity. Implementation sticking fingerprints do Civil Registry Office has a mechanism and standard operating procedure from the stage of registration, data entry and verification of data so that the results can be used as the information and valid. But sticking obligation fingerprint notaries do is rely on the interpretation of each requires a considerable time in the match the data client  Purpose, Fingerprints, Public Administration